2019
DOI: 10.1017/s0021859619000650
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the farm-level economic costs of spring cropping to manage Alopecurus myosuroides (black-grass) in UK agriculture

Abstract: Crop rotation is a non-chemical strategy adopted by farmers to manage weeds. However, not all crops in a rotation are equally profitable. Thus, there is potentially a trade-off between the costs and benefits of this strategy. The objective of the current study is to quantify this trade-off for the rotational control of an important weed (Alopecurus myosuroides). Data from 745 farms were used to parameterize a farm-level mixed-integer goal-programming model of the economics of spring cropping for weed control i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Some of these resultant impacts are soil erosion, soil degradation, depletion of nutrients, pest and disease infestation, soil impaction etc. [32]; [33]; [34]. The soil support both crop and weed species and both inter-relate in the course of growth and development for nutrients, space, light, water [35].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these resultant impacts are soil erosion, soil degradation, depletion of nutrients, pest and disease infestation, soil impaction etc. [32]; [33]; [34]. The soil support both crop and weed species and both inter-relate in the course of growth and development for nutrients, space, light, water [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, modeling simulations have been shown to reduce glyphosate resistance in Palmer amaranth by two-fold if glyphosate-tolerant (GR) cotton is rotated with GR corn [60]. An increasing number of herbicide-resistant weeds left farmers with fewer herbicide options; for instance, farmers in the United Kingdom are adopting crop rotation in spring to control herbicide-resistant blackgrass (Alopecurus myosuroides) [61]. A survey in Germany indicated that 89% of the farmers use crop rotation to control or prevent herbicide resistance [62].…”
Section: Crop Rotationmentioning
confidence: 99%
“…We tackle the problem of modelling the population dynamics of a damaging arable weed (black‐grass, Alopecurus myosuroides ) in response to management across multiple sites using incomplete data. Black‐grass is a particularly problematic weed in western Europe, where over the past 30 years it has evolved target and non‐target site resistance to multiple herbicides (Comont et al., 2019; Délye et al., 2010, 2011; Hicks et al., 2018; Kemp et al., 1990; Menchari et al., 2007), and causes severe economic damage (Ahodo et al., 2019; Varah et al., 2020). We include management variables that describe herbicide pressure, cultural control via cultivation and cropping, and the timing of interventions, alongside data on herbicide resistance and soil quality.…”
Section: Introductionmentioning
confidence: 99%